Retention of periodontally hopeless tooth and the clinical effect on the adjacent tooth at maintenance phase: A retrospective study - Jaafar, Mohamad Adib; Ahmad Yaziz, Yuhaniz; Abdul Manab, Enny Esdayantey (IIUM Journal of Orofacial and Health Sciences, 2022)
Previous research has shown that periodontal maintenance therapy can keep teeth healthy for a long time. However, only a few studies have been conducted on the periodontal hopeless tooth that is retained during the maintenance phase. The purpose of this study was to evaluate if retaining a periodontal hopeless tooth had an effect on the periodontal conditions in the adjacent tooth at maintenance. A retrospective analysis was conducted on the periodontal status of periodontitis patients who presented with retained hopeless tooth. Hopeless prognosis is based on the mean percentage of the mesial and distal radiographic bone loss ? 65%. The periodontal status consists of periodontal pocket depth (PPD), clinical attachment loss (CAL), and bleeding on probing (BoP), which were evaluated at baseline (T0), after active therapy (T1) and at the last examination (T2) for both the hopeless tooth and the tooth/teeth adjacent to it. Compliance toward maintenance and reason for hopeless tooth extraction were also evaluated at maintenance (T1-T2). A total of 65 patients with 121 hopeless teeth and 187 adjacent teeth were included. Significant improvement of all periodontal parameters for both hopeless and adjacent teeth at T1 and T2 from T0 were observed within 5.05±2.58 years of observation, except for the CAL during maintenance. In conclusion, a low risk of disease progression on the tooth adjacent to the retained periodontal hopeless tooth can be achieved following active treatment with strict maintenance care.